COVID-19 among Czech Dentistry Students: Higher Vaccination and Lower Prevalence Compared to General Population Counterparts - Schmidt, Jan; Vavrickova, Lenka; Micopulos, Christos; Suchanek, Jakub; Pilbauerova, Nela; Perina, Vojtech; Kapitan, Martin (Vaccines, 2022)
The restrictions on medical students’ clinical education during the COVID-19 pandemic has affected their professional readiness and often lengthened their training. These negative impacts are often considered a necessary price as clinical education is hypothesized to be associated with a high risk of pandemic spread. This work assesses this hypothesis based on COVID-19 epidemiological data among Czech dentistry students and their comparison to data of the Czech general population of similar age. We addressed two of the five Czech medical faculties (Charles University, Faculty of Medicine in Hradec Kralove and in Pilsen) providing dentistry study program with a survey. A total of 240 students participated, representing a 66.9% response rate. Over 75% of respondents participated in clinical education during the pandemic. The school environment was identified as a place of infection by only 9.8% of respondents who were aware of where they were infected. Overall, 100% of students used FFP2 respirators, and 75.3% used face shields or protective glasses while working with patients. By the end of May 2022, COVID-19 full vaccination and 1st booster rates among students were 93.8% and 54.6%, respectively, which is significantly higher (p < 0.0001, OR 7.3, 95% CI 4.4−12; p < 0.0001, OR 3.7, 95% CI 2.9−4.8, respectively) compared to their peers from the general population (67.1% and 24.4%, respectively). A total of 75.4% of respondents supported mandatory COVID-19 vaccination for healthcare professionals. To the same date, PCR and/or antigen test verified COVID-19 prevalence among students was 37.1%, while among peers from the general population, it was 45.1% (p = 0.015, OR 1.2, 95% CI 1.0−1.5). The combination of extensive protective measures and high vaccination against COVID-19 led to significantly lower COVID-19 prevalence among the students compared to their general population counterparts.
Keywords: students; prevalence; vaccination; dentistry; COVID-19